2011
DOI: 10.4038/tapro.v2i2.3146
|View full text |Cite
|
Sign up to set email alerts
|

Reptile diversity of a fragmented lowland rain forest patch in Kukulugala, Ratnapura district, Sri Lanka

Abstract: A four month survey was undertaken to document the diversity and abundance of reptiles in the Kukulugala forest (KF) in the Ratnapura District, Sri Lanka. A total of 708 individuals belonging to 41 genera (~50%) and 13 families (~55%) were recorded. KF had high species diversity with 58 species, representing about ~28% of the total diversity of known reptiles of Sri Lanka. Of the recorded species, 11 (~19%) were threatened and 24 (~44%) are endemic to Sri Lanka. Endemic relict genera including Aspidura, Balano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Karunarathna et al (2004) observed this species at Kukulugala (Sabaragamuwa Province) and Ritigala (Northcentral Province). Later, Karunarathna & Perera (2010) and Karunarathna & Amarasinghe (2010) recorded it from Nilgala (Uva Province) and Eluwankulama (Northwestern Province). We additionally observed L. calamaria at Paalaviya-Puttalam (Northwestern Province), Duviliella-Kaltota (Uva Province), Wasgomuwa (Northcentral Province), Udawalawa (Uva Province), and Minneriya (North-central Province).…”
Section: Redescription Of Liopeltis Calamaria Indicamentioning
confidence: 97%
“…Karunarathna et al (2004) observed this species at Kukulugala (Sabaragamuwa Province) and Ritigala (Northcentral Province). Later, Karunarathna & Perera (2010) and Karunarathna & Amarasinghe (2010) recorded it from Nilgala (Uva Province) and Eluwankulama (Northwestern Province). We additionally observed L. calamaria at Paalaviya-Puttalam (Northwestern Province), Duviliella-Kaltota (Uva Province), Wasgomuwa (Northcentral Province), Udawalawa (Uva Province), and Minneriya (North-central Province).…”
Section: Redescription Of Liopeltis Calamaria Indicamentioning
confidence: 97%
“…Visual observations were conducted by searching 20 cm deep into the leaf litter (Figure 1). A comprehensive exploration was conducted across diverse habitats, encompassing water bodies, rock crevices, logs, trees, decaying vegetation, and bushes up to 5 metres in height, as well as the tree canopy, to detect reptiles, birds, mammals, fish, butterflies, dragonflies, snails, and amphibians (Karunarathna and Amarasinghe, 2011). The identification process involves the comparative method which allows a systematic approach used in faunal diversity studies especially compares the physical characteristics, behaviours and genetic details (Early-Capistrán et al, 2020;Munari and Mistri, 2008), and all species and colour variations were documented in live photographs using digital singlelens reflex cameras (Canon 80D and 600D).…”
Section: Data Collectionmentioning
confidence: 99%
“…This region comprises a natural forest that still accounts for slightly more than 12% of the total land area (Premakantha et al, 2021). Environmental factors, including substantial rainfall, humidity, and dense undergrowth, are prevalent in these areas, providing a conducive environment for a diverse array of fauna (Karunarathna and Amarasinghe, 2011;Ranagalage et al, 2020). Nonetheless, the island's native forests are rapidly declining due to the expansion of settlements and agricultural land, resulting in detrimental effects on its rich biodiversity (Rodrigo and Manamendra-Arachchi, 2020).…”
Section: Introductionmentioning
confidence: 99%